2017
DOI: 10.1155/2017/3480234
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokeratin 18 M30 Levels in Chronic Hepatitis B Reflect Both Phase and Histological Activities of Disease

Abstract: Chronic hepatitis B has highly a dynamic course with significant fluctuations of HBV-DNA and ALT impeding assessment of disease activity. New biomarkers of inflammatory versus noninflammatory stages of HBV infection are urgently needed. Cytokeratin 18 epitope M30 (M30 CK-18) is a sensitive marker of cell death. We aimed to investigate an association between serum M30 CK-18 and histological activity and phase of HBV infection. 150 Caucasian patients with HBV-infection were included in the study. Serum M30 CK-18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
2
6
0
1
Order By: Relevance
“…6 Swiderska M and his colleges found altered levels of CK18 depending upon the severity of disease inspite of having normal serum ALT. 10 Incontrast to this, our study found positive association of CK18 with serum ALT. Study conducted by Alt Y and his colleagues are in agreement to our results concerning serum ALT as they reported similar association.…”
Section: Discussionsupporting
confidence: 75%
“…6 Swiderska M and his colleges found altered levels of CK18 depending upon the severity of disease inspite of having normal serum ALT. 10 Incontrast to this, our study found positive association of CK18 with serum ALT. Study conducted by Alt Y and his colleagues are in agreement to our results concerning serum ALT as they reported similar association.…”
Section: Discussionsupporting
confidence: 75%
“…A high proportion of upper tertile of cK18 and K18 was observed throughout the entire hospitalization.4 | D ISCUSS I ONKnowledge of hepatocyte death in the background of HBV infection is limited. Our previous study and others confirmed that hepatocyte cell death as evaluated with serum biomarkers, K18 (total cell death) and cK18 (apoptosis), is closely associated with hepatic inflammation and HBV DNA activity in relative stable stage without complications of cirrhosis 23,41,42. However, in the stage of decompensated cirrhosis with HBV infection, the varied HBV DNA activity, hepatic insufficiency, portal hypertension, altered immunopathology and hepatic and extra-hepatic organ dysfunction/failure make the profile of hepatocyte death rather intricate.…”
supporting
confidence: 56%
“…Increased levels of M30 as a marker of apoptosis predicted non-hepatocellular carcinoma liver-related mortality in patients with alcoholic cirrhosis [ 20 ]. The predictive and prognostic value of M30 in patients with different liver diseases was studied previously [ 43 47 ]. We investigated the predictive value of pre-transplant M30 and M65 levels in cirrhotic patients with different original diseases.…”
Section: Discussionmentioning
confidence: 99%